2021
DOI: 10.1002/tcr.202100023
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on the Synthesis of Chiral Sulfones

Abstract: Chiral sulfones extensively exist in drugs, agricultural chemicals, chiral organic intermediates, and functional materials. Their importance causes the rapid development of their synthetic methods in recent years. Many transition metal complex catalysts with chiral ligands and chiral organocatalysts are adopted in synthesis of chiral sulfones. Most of the methods to construct chiral sulfones are based on the reduction of unsaturated sulfones and the introduction of sulfone groups into unsaturated hydrocarbons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Next, a set of solvents were investigated. The results showed that other solvents like toluene, THF, 1,4-dioxane and MeCN were far less effective than alcohols (Table 1, entries [7][8][9][10][11][12]. Furthermore, examination of the base indicated that switching CH 3 COONa to others led to an obvious decrease in the reaction yield, albeit similar ee values (Table 1, entries [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, a set of solvents were investigated. The results showed that other solvents like toluene, THF, 1,4-dioxane and MeCN were far less effective than alcohols (Table 1, entries [7][8][9][10][11][12]. Furthermore, examination of the base indicated that switching CH 3 COONa to others led to an obvious decrease in the reaction yield, albeit similar ee values (Table 1, entries [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…5 Typically, apremilast, a drug for the treatment of plaque psoriasis and psoriatic arthritis, was synthesized from a chiral β-hydroxy sulfone via the Mitsunobu reaction. 6 On account of the considerable use of chiral β-hydroxy sulfones, many methods have been developed for their asymmetric synthesis in the past few years, 7 including resolution of racemic β-hydroxy sulfones, 8 enzyme-mediated oxidation and reduction of β-hydroxy sulfones, 9 asymmetric reduction of β-keto sulfones, 10 transition-metal-catalyzed asymmetric hydrogenation (AH), 11 and asymmetric transfer hydrogenation (ATH). 12 Among them, the transition-metal-catalyzed AH reaction is one of the most economical, practical, and convenient methods to prepare chiral β-hydroxy sulfones, possessing 100% atom economy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Zeng reported a comprehensive review on the progress in the synthesis of various chiral sulfones products. [19] Very recently, Jiang reported the research advances of chiral sulfones with sulfone parts directly connected to stereocenters since 2010. [20] Different from the two reviews starting from the structure of chiral sulfone, this review focuses on the synthetic methods of chiral sulfones.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, various synthesis methods about enantioenriched sulfone also have been widely reported, but the relevant reviews are few in this aspect. In 2021, Zeng reported a comprehensive review on the progress in the synthesis of various chiral sulfones products [19] . Very recently, Jiang reported the research advances of chiral sulfones with sulfone parts directly connected to stereocenters since 2010 [20] .…”
Section: Introductionmentioning
confidence: 99%
“…The latter enables their transformation into other functional groups and further derivatization. Several strategies involving asymmetric hydrogenation have been used to construct chiral sulfones . Outstanding enantioselectivities were achieved in the iridium-based asymmetric hydrogenation of sulfones reported by Andersson and co-workers .…”
mentioning
confidence: 99%